Regimes of science production and diffusion: towards a transverse organization of knowledge (Scientiae Studia, 2012)
This article is a contribution to the critical sociology of science perspective introduced and developed by Pierre Bourdieu. The paper proposes a transversalist theory of science and technology production and diffusion. It is here argued that science and technology are comprised of multiple regimes where each regime is historically grounded, possesses its own division of labour, modes of cognitive and artifact production and has specific audiences. The major regimes include the disciplinary regime, utilitarian regime, transitory regime and research-technology regime. Though each regime is autonomous, they are simultaneously closely interlaced. In science and technology, autonomy is not antithetical to interdependence and reciprocity. This study demonstrates for the four specified regimes of production and diffusion that differentiation is not contrary to interaction. In science, differentiation and interaction comprise two sides of the same coin. All regimes exhibit a measure of transversality.